THE EFFECTS OF ROA, ROE, NPL, AND OPERATING EXPENSES TO OPERATING REVENUES ON STOCK RETURN AT COMMERCIAL BANKS IN INDONESIA - Iskandar, Yusuf (Jurnal Aplikasi Manajemen, 2020)
Stock return is one indicator to show the performance of banks in Indonesia. This study aimed to empirically examine the effect of return on assets (ROA), return on equity (ROE), non-performing loans (NPL), and operating expenses to operating revenues on stock returns on commercial banks listed on the Indonesia Stock Exchange (IDX) years 2016-2018. For this reason, as many as 15 banks that meet the criteria were taken as samples in this study. The collected data were then analyzed using multiple regression analysis to test the proposed hypotheses. Several findings in this study indicated that each element, namely returns on assets, return on equity, non-performing loans, and operating expenses to operating revenues, respectively, had a significant effect on stock returns. Based on these findings, it was recommended that banking companies could manage financial ratios optimally to maximize stock return.